THE IMPORTANCE OF STATE ECONOMIC POLICY AND SMALL BUSINESS IN INCREASING EMPLOYMENT (Universal International Scientific Journal, 2026)
This article explores the multi-dimensional role of state policy, educational institutions, and private sector initiatives in increasing employment, with a specific focus on the case of Uzbekistan. Drawing on national statistics and international best practices, the study examines employment trends from 2020 to 2023 and identifies key drivers of job creation such as vocational education, entrepreneurship promotion, and digital economy development. The literature review highlights how technological innovation, gender inclusion, and skills alignment have become central to modern labor market strategies. The discussion section offers a critical analysis of the structural challenges facing Uzbekistan’s labor market, including informal employment, youth unemployment, and the mismatch between education and industry needs. Based on these findings, the article proposes a set of policy recommendations aimed at improving the quality, inclusiveness, and sustainability of employment in both urban and rural contexts. The research emphasizes the need for holistic, cross-sectoral coordination to ensure long-term employment growth in a transitioning economy. Keywords: employment growth, vocational education, labor market, skills mismatch, informal sector, youth unemployment, gender inclusion, policy reform, digital economy, sustainable development.
Keywords: employment growth, vocational education, labor market, skills mismatch, informal sector, youth unemployment, gender inclusion, policy reform, digital economy, sustainable development.